2014
DOI: 10.1080/14786419.2014.949705
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic composition and antioxidant activity of propolis from various regions of Poland

Abstract: The aim of this work was to determine phenolic acid and flavonoid contents, as well as antioxidant properties of propolis from different regions of Poland. Total phenolic content of propolis samples ranged from 150.05 to 197.14 mg/g GAE, while total flavonoid content was 35.64-62.04 mg/g QE. The dominant phenolic acid was p-coumaric acid, the content of which was from 37.54 to 116.95 mg/g. The samples also contained much ferulic acid. Among the flavonoids, chrysine and galangine were dominant, and for two samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
74
2
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(102 citation statements)
references
References 22 publications
18
74
2
8
Order By: Relevance
“…The herbal with the highest amount of flavonoids among the products studied is Propolis from UK, 35mg Q / g of propolis dry extract. The amount of flavonoids in UK propolis is in the range of flavonoids found in samples from Poland [43]. Brazilian propolis presents fewer amounts of flavonoids than the UK one, which could be confirmed by the FTIR.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The herbal with the highest amount of flavonoids among the products studied is Propolis from UK, 35mg Q / g of propolis dry extract. The amount of flavonoids in UK propolis is in the range of flavonoids found in samples from Poland [43]. Brazilian propolis presents fewer amounts of flavonoids than the UK one, which could be confirmed by the FTIR.…”
Section: Discussionsupporting
confidence: 60%
“…104, l. [41][42][43][44] [1]), healing "involves platelet aggregation and blood clotting, formation of fibrin, an inflammatory response to injury, alteration in the ground substances, angiogenesis and re-epithelialization". To heal, the wound / the burn needs to be free of infection.…”
Section: Introductionmentioning
confidence: 99%
“…A high correlation between the total phenolic and flavonoid content and free radical scavenging activity was also reported for propolis samples from other countries; e.g., Argentina (Vera et al 2011), Japan (Hamasaka et al 2004), Greece and Cyprus (Popova et al 2005), and Poland (Socha et al 2015). Correlations between individual compounds and antioxidant and antimicrobial activity were also analysed ( Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…TPC values of these samples was between 10.94 and 79.23 mg GAE/g propolis. 30 TPC and TFC values of propolis extracts have been reported that as 174.7 mg GAE/g dry sample, 45.1 mg QE/g dry sample from China, 31 between 150-197 mg GAE/g dry sample, 35.64-62.04 mg QE/g dry sample from Poland, 32 and 31.2-299 mg GAE/g dry sample, 2.5-176 mg QE/g dry sample from other parts of the world, respectively.…”
Section: Discussionmentioning
confidence: 99%